KEDUDUKAN HADITH DALAM JUZUK 2 KITAB KASYF AL-GHUMMAH FI AHWALIL MAUTA FIL BARZAKH WAL QIYAMAH - Muhammad Darul Ehsan Derome; Mohd Arif Nazri (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2017)
This study examines the position of hadith of chapter 16 in the second volume of the Book of Kasyf al-Ghummah Fi Ahwalil Mauta Fil Barzakh Wal Qiyamah by Syeikh Daud al-Fatani. The research shows that Sheikh Daud wrote this book to answer the demands of the people who wanted to know about death and doomsday. The characteristics of this book present a number of hadiths without specifying the position of the hadith. The findings of the 16 Hadiths find 3 Hadiths of Muttafaqun alaih, 7 are sahih, 1 is hasan, 2 hadiths are dhaif, 3 hadiths are not known to their original sources. Among the 13 hadiths found its source, 11 hadith are maqbul and 2 are mardud.